The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1186/s12909-023-04048-z
|View full text |Cite
|
Sign up to set email alerts
|

Ticket to perform: an explorative study of trainees’ engagement in and transfer of surgical training

Abstract: Background Research suggests that simulation-based surgical skills training translates into improved operating room performance. Previous studies have predominantly focused on training methods and design and subsequent assessable performances and outcomes in the operating room, which only covers some aspects of training engagement and transfer of training. The purpose of this qualitative study was to contribute to the existing body of literature by exploring characteristics of first-year traine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Multiple groups have shown that playing serious games and spending time in surgical simulation labs, both under the supervision of expert surgeons or using portable training devices, ultimately improves performance on surgical VR simulation tasks [31][32][33][34]. However, even with demonstrated high performance on VR simulation tasks, trainees report that the bar to entry in the OR remains the lack of opportunities to apply their skills in vivo and their relationships with training physicians [35].…”
Section: Innovation In Simulation For Urologic Proceduresmentioning
confidence: 99%
“…Multiple groups have shown that playing serious games and spending time in surgical simulation labs, both under the supervision of expert surgeons or using portable training devices, ultimately improves performance on surgical VR simulation tasks [31][32][33][34]. However, even with demonstrated high performance on VR simulation tasks, trainees report that the bar to entry in the OR remains the lack of opportunities to apply their skills in vivo and their relationships with training physicians [35].…”
Section: Innovation In Simulation For Urologic Proceduresmentioning
confidence: 99%